Water availability for high yield of soybean cultivars (Research, Society and Development, 2020)
Considering the hypothesis that soybean cultivars present different yield potential, even under ideal water conditions, this study aimed to identify highly productive soybean cultivars under optimal conditions of soil moisture management. Two experiments were conducted in the 2015/16 and 2016/17 crop seasons in Chapadão do Sul-MS, in a complete  In a split-plot arrangement design with four replications. In the first experiment, the plots was composed of six water application frequencies (0, 1, 2, 3, 4, and 5 days); in the second experiment, the primary factor was constituted by six supplementary irrigation levels (0, 25, 50, 75, 100, and 125% of the Crop Evapotranspiration - ETc). In each experiment, subplots was composed of  five soybean cultivars. The following variables were evaluated: plant height, insertion of the first pod, hundred grain weight, and grain yield. Regardless of the irrigation management used, soybean cultivars presented different agronomic performance.